2022
DOI: 10.1039/d1qo01705e
|View full text |Cite
|
Sign up to set email alerts
|

Euphorstranoids A and B, two highly rearranged ingenane diterpenoids from Euphorbia stracheyi: structural elucidation, chemical transformation, and lipid-lowering activity

Abstract: Euphorstranoids A (1) and B (2), two highly rearranged ingenane diterpenoids with an unusual 5/6/7/3 carbon ring system, were isolated from Euphorbia stracheyi. Their structures were determined by a combination...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Euphylonane J (10) had the molecular formula C 41 H 40 O 9 as derived from HRESIMS analysis (m/z 699.2585 [M + Na] + , calcd 699.2565). Comparison of its NMR spectroscopic data (Table 3) with those of euphoglonane B (18) revealed that one of the gem-dimethyls in 18 was replaced by a benzoyloxymethyl group in 10, 31 3) were comparable with those of 10, with the main differences being from an elimination of one of the three benzoyl groups in 10 and the upfield-shifted H-5 signal in 11 (δ H = 5.46 in 10 and 3.49 in 11), suggesting that 11 was a 5-O-debenzoylated analogue of 10. This assumption was secured by the observation of HMBC correlations (Figure S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Euphylonane J (10) had the molecular formula C 41 H 40 O 9 as derived from HRESIMS analysis (m/z 699.2585 [M + Na] + , calcd 699.2565). Comparison of its NMR spectroscopic data (Table 3) with those of euphoglonane B (18) revealed that one of the gem-dimethyls in 18 was replaced by a benzoyloxymethyl group in 10, 31 3) were comparable with those of 10, with the main differences being from an elimination of one of the three benzoyl groups in 10 and the upfield-shifted H-5 signal in 11 (δ H = 5.46 in 10 and 3.49 in 11), suggesting that 11 was a 5-O-debenzoylated analogue of 10. This assumption was secured by the observation of HMBC correlations (Figure S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Biogenetically, the assignment of the stereochemistry of 1 and 2 was in agreement with that of a common precursor, the co-isolated new ingenane (6) (Scheme S1). 26,27 (18) were readily assembled by corresponding COSY cross-peaks, which, in combination with the HMBCs from H-4, H-7, H 2 -12, and H 3 -18 to C-9, from H 2 -5 and H-8 to C-10, and from H 3 -20 to C-5, C-6, and C-7, facilitated the establishment of a 7/6 fused (B/ C) ring system. Furthermore, the HMBCs from both H 2 -16 and H 3 -17 to C-13, C-14, and C-15 constructed a cyclopentane fragment, attaching a hydroxymethyl (16-CH 2 OH) and a methyl (Me-17) group at C-15.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…209 Euphorstranoids A and B ( 994 and 995 ), possessing an unusual 5/6/7/3 carbon ring system, might be derived from two consecutive 1,2-carbon shift rearrangements of euphstrachenol C ( 744 ), a co-occurring diterpenoid. 210 Euphorikanin A ( 996 ), a novel 5/6/7/3-fused tetracyclic diterpenoid lactone, was isolated from the roots of E. kansui . 211 Its biosynthetic precursor was supposed to be the co-isolated ingenane diterpenoid, 4- O -acetyl-5- O -benzoyl-3β-hydroxy-20-deoxyingenol.…”
Section: Isolated Diterpenoidsmentioning
confidence: 99%
“…Croton yunnanensis W. W. Smith (Euphorbiaceae) is a shrub distributed in the southwest provinces of mainland China . Previous phytochemical investigations of this plant revealed diterpenoids and sesquiterpenoids as the major metabolites, of which some showed selective cytotoxicity against three tumor cell lines, SMMC-7721, HL-60, and A549. , In our continuing efforts toward obtaining novel diterpenoids from plants in the family Euphorbiaceae, a 19- nor -clerodane diterpenoid dimer ( 1 ) featuring a C-16–C-12′ linkage, along with its precursor ( 2 ), were isolated from C. yunnanensis . Their structures (Figure ) were elucidated by spectroscopic, computational, and single-crystal X-ray diffraction methods.…”
mentioning
confidence: 99%